The motives of travelling among the Netherlands tourists to Langkawi Island, Malaysia - Muhamad Nasir, Muhamad Nasyat; Azwa Mohd Zain, Fahru; Izzati Ab Ghani, Nur (Ateliê Geográfico, 2024)
The main objective of the study is to determine the motives of travelling among the Netherlands tourists and its effect on tourist satisfaction, place attachment and destination loyalty towards the Jewel of Kedah (Langkawi Island). A total of 304 respondents were participated in the questionnaire survey at the Airport. The respondents were selected based on purposive and simple random sampling.Structural Equation Modelling was executed to analyze the data.It was found that tourist satisfaction is acting as a partial mediator between tourist motivation and place attachment relationship. This is relatively a unique contribution because a few studies in the past have tested this mediating effect. The study also found a direct relationship of place attachment on destination loyalty. The study recommends tourism management in Langkawi to address and promote the locals’ culture and lifestyle in order to motivate the Netherlands tourists to visit the destination, which could satisfy and build a strong connection between the tourists and the island.